DAMPAK PANDEMI COVID-19 TERHADAP MANAJEMEN DAN STRATEGI PEMASARAN SAYUR ORGANIK (Studi Kasus di Kelompok Tani Tranggulasi Desa Batur, Kabupaten Semarang) - Illene Naomi Nugroho; Yuliawati Yuliawati (Universitas Galuh Ciamis, 2021)
Today's a lot of people are starting to pay attention to consumed products such as organic vegetables. The emergence of covid-19 has an impact on the sale of organic vegetables. One of the business actors who have experienced the impact of Covid-19 is the Tranggulasi farmer group. Tranggulasi is engaged as a producer and supplier of organic vegetables in several cities. The emergence of Covid-19 had an impact on the sale of organic vegetables. The purpose of this study is to examine the impact of the Covid-19 pandemic on the management and marketing strategies of organic vegetables in Tranggulasi. The research method used is descriptive analysis, marketing mix (4P), and Analytical Hierarchy Process (AHP). Based on the research results, the impact of Covid-19 on management is the difficulty of distributing organic vegetables, selling dynamic products, and maximizing sales with social media. Based on the results of AHP analysis at the factor level, the product is the main focus with a weight of 0.29. Level of actors, secretaries with a weight of 0.44. The priority objectives in the marketing strategy are improving quality and quality with a weight of 0.29. At the alternative level, setting product quality standards is a priority with a weight of 0.37.